Nanosized niosomes as effective delivery device to improve the stability and bioaccessibility of goat milk whey protein peptide. (November 2022) - Du, Xiaojing; Huang, Xin; Wang, Li; Mo, Ling; Jing, Huijuan; Bai, Xinpeng; Wang, Hongxin
Graphical abstract: Highlights: Goat milk whey protein peptides (GWP, <3 kDa) had stronger hypoglycemic activity. GWP was encapsulated into niosomes using 4 phytosterols replace cholesterol. Morphologically confirmed GWP was successfully loaded into liposomes and niosomes. GWP niosomes have high simulated gastrointestinal and long-term storage stability. GWP niosomes can significantly improve the bioaccessibility of GWP. Abstract: This study sought to develop a nanoscale delivery system to enhance the stability and bioaccessibility of goat milk whey protein peptides. Goat milk whey protein was hydrolyzed by papain, and the hydrolysate was ultrafiltered to obtain a low molecular weight peptide (GWP, <3 kDa) with strong hypoglycemic activity. The GWP-loaded liposomes and niosomes encapsulation systems were prepared using phytosterols (ergosterol, β- sitosterol, mixed phytosterols, and stigmasterol) instead of cholesterol. Results showed that the GWP-loaded niosomes (GWP-NS) prepared from β- sitosterol had the higher GWP encapsulation efficiency (90.46 ± 4.02 %) and the smaller particle size (92.07 ± 9.8 nm) than liposomes (GWP-LS). Additionally, the morphological results showed that two GWP-loaded systems were smooth and spherical, and the FT-IR spectroscopy confirmed the successful formation of the peptide-loaded system. Compared with GWP, GWP-LS and GWP-NS showed the higher stability under different pH, temperature, and NaCl concentration conditions, especially GWP-NS. Furthermore, GWP-NS could significantly improve the retention rate of GWP during simulated gastrointestinal digestion, in vitro bioaccessibility, and hypoglycemic activity. These findings suggest that β- sitosterol could be a potential membrane stabilizer alternative to cholesterol, and GWP niosomes could be a potential new drug delivery system.